Hydrocarbon Biogeochemical Setting of the Baffin Island Oil Spill Experimental Sites. II. Water - Cretney, Walter J.; Green, David R.; Fowler, Brian R.; Humphrey, Blair; Fiest, David L.; Boehm, Paul D. (ARCTIC, 1987)
A baseline for petroleum residues in the waters of the Cape Hatt region of Baffin Island in arctic Canada was obtained in anticipation of controlled oil releases of the Baffin Island Oil Spill (BIOS) Project. Total aliphatic and aromatic residues reflecting multiple sources were found to be in the low to sub micro g/l concentrations range. Alkylated naphthalenes, phenanthrenes and dibenzothiophenes were present in the sub ng/l concentrations range. The hydrocarbon baseline for the waters of the BIOS study area was found to be as low as might be found anywhere on earth and therefore ideally suited to the BIOS study.Key words: BIOS, arctic marine Canada, hydrocarbon baseline, water Mots clés: BIOS, Arctique marin canadien, niveau de référence d’hydrocarbures, eau